2009
DOI: 10.2478/s11756-009-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Activity of selected hydrolytic enzymes from leeches (Clitellata: Hirudinida) with different feeding strategies

Abstract: Hydrolase activities of extracts from different parts of the bodies of parasitic (Theromyzon tessulatum, Piscicola geometra) and predatory (Erpobdella octoculata, Glossiphonia complanata) leeches were examined. The highest activity was detected in the extracts from sections containing the intestine. Hydrolase activities in the crop and intestine of parasitic leeches were higher than in predatory leeches. The high activity of most of hydrolases in those segments may indicate the intensity of digestion and absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…These enzymes are involved in the digestion of numerous nourishments. Our study revealed that the number of active enzymes in the crop of leeches that parasitize fish and predatory leeches is similar (17 to 18 enzymes), as reported by Dziekońska et al (2009). Moreover, we observed a very low level or absence of trypsin and α-chymotrypsin activity in the crop of all the leeches analyzed during our study.…”
Section: Differences In Enzyme Activity Among Various Regions Of the Digestive System Of The Studied Taxasupporting
confidence: 88%
See 3 more Smart Citations
“…These enzymes are involved in the digestion of numerous nourishments. Our study revealed that the number of active enzymes in the crop of leeches that parasitize fish and predatory leeches is similar (17 to 18 enzymes), as reported by Dziekońska et al (2009). Moreover, we observed a very low level or absence of trypsin and α-chymotrypsin activity in the crop of all the leeches analyzed during our study.…”
Section: Differences In Enzyme Activity Among Various Regions Of the Digestive System Of The Studied Taxasupporting
confidence: 88%
“…glucose) are absorbed in the crop of P. geometra. Moreover, enzymatic (Dziekońska et al 2009) and ultrastructural studies (Rost-Roszkowska et al 2012) showed that digestion and absorption occur in the crop of these leeches. This statement was confirmed in our study as in the crop of the analyzed species (except B. astaci) the activity of acid and alkaline phosphatases was detected.…”
Section: Differences In Enzyme Activity Among Various Regions Of the Digestive System Of The Studied Taxamentioning
confidence: 99%
See 2 more Smart Citations
“…In most parasitic leeches the host blood is stored in the crop, while food digestion and the absorption of nutrients occur predominantly in the intestine. It can be assumed that medicinal leech enzymes (e.g., endopeptidases, aminopeptidases, phosphatases) promote digestion processes [14].…”
mentioning
confidence: 99%